Great correlation: Biodegradation and chemotactic adsorption of Pseudomonas synxantha LSH-7' for oil contaminated seawater bioremediation. (15th April 2019) - Meng, Long; Li, Wen; Bao, Mutai; Sun, Peiyan
Abstract: Oil Contaminated Seawaters is treated by biological processes of sorption or degradation. Considering the chemotaxis of bacteria, they migrate towards a better way to survive. However, the information concerning the chemotactic biosorption of microorganism is severely limited thus far. Therefore, chemotactic biosorption a novel way of sorption was put forward. The equation was defined as: Achemotactic biosorption = Aextracellular biosorption - Apassive extracellular biosorption + Eintracellular . Effects of controlling parameters like pollutant, fertilizer, sediments and surfactant on bacterial chemotactic sorption capacity of tetradecane, hexadecane, phenanthrene or pyrene were described in detail. The results showed bacterial chemotactic biosorption would be promoted under the conditions of low pollutant concentration, high sediment concentration and fertilizer. However, Tween 80 would promote the sorption of pollutants onto bacterial cells depending on the concentration of surfactant. Correlational analyses were conducted with the biodegradation rate and the concentration (mg/g) of hydrocarbons measured in the biomass. We concluded there existed great correlation between them. Biodegradation rate were all linearly correlated with the concentration (mg/g) of hydrocarbons measured in the biomass in all respects with tetradecane (R 2 = 0.9873), hexadecane (R 2 = 0.9705), phenanthrene (R 2 = 0.9098) and pyrene (R 2 = 0.9424). The above idea may provide a new insight into oil spill bioremediation from sorption to degradation. Graphical abstract: Image 1 Highlights: Chemotactic biosorption a novel way of sorption was put forward. Effects of controlling parameters on chemotactic adsorption were investigated. Fertilizer, low pollutant and high sediment enhanced chemotactic biosorption. Maximum of chemotactic sorption by Tween 80 was at critical micelle concentration. Biodegradation rate was linearly correlated with chemotactic adsorption (mg/g).